Characterization of residue from EFB and Kenaf Core Fibres in the liquefaction process - Sarani Zakaria; Rasidi Roslan; Umar Adli Amran; Chin, Hua Chia; Saiful Bahari Bakaruddin (Universiti Kebangsaan Malaysia, 2014)
Different type of fibers which is EFB and KC were liquefied in phenol with the presence of sulphuric acid as a catalyst. The liquefied residue was characterized by using Fourier transform infrared (FTIR) to determine the functional groups presents in both residues, X-ray diffraction (XRD) to determine the degree of crystallinity in the residue, thermogravimetric analysis (TGA) to analyze the thermal properties of the residue and scanning electron microscope (SEM) to investigate the structure and morphology of the residue. Phenol-to-EFB/KC ratio shows great effect on the amount of residue in the liquefaction process. Peak appearance can be observed in the FTIR analysis at 810 and 750 cm-1 which is attributed to the para and meta benzene, respectively or to be specific its associated to the p-alkyl phenol and m-alkyl phenol. In the XRD analysis, CrI of lignocellulosic materials increased after liquefaction process. Liquefaction process caused chemical penetration across the grain of the fiber, thus the fiber bundles started to separate into individual fibers shown in the SEM micrograph and the weights lost curve for both liquefied EFB and KC experienced three region decompositions.